The International Responsibility for Repelling Boat Refugees - Mohammed, Wasan; Wali, Baydaa (Journal of Legal Sciences, 2023)
The maritime borders of the coastal state are the scene of the human tragedies that we are witnessing in the context of the perilous plight of refugees at sea، and the failure to help people at risk by the coastal state will entail international responsibility towards them، and the three international maritime conventions، commitments aimed at coastal states with the duty to provide assistance and rescue to persons in danger of being lost at sea، is without doubt one of the most basic principles established in the law of the sea، in addition to establishing and operating And maintenance of the search and rescue service، and not to expel them and return them to their country of origin or another country.